Tujuan Pendidikan Islam Menurut Al-Ghazali Ditinjau dari Perspektif Hadis (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2021)
The purpose of education is a component that we must know and understand in life. This has been discussed by scholars, including Imam al-Ghazali. For this reason, this study discusses the goals of Islamic education according to al-Ghazali from the perspective of Hadith. This research is a library research, namely research that uses data sources from library searches in the form of books and articles, namely the books of Hadith and their syarah, as well as the Nabawiyah sirah. The approach used is, by using qualitative data analysis methods. While the data collection technique in this study is a documentation technique, namely by collecting hadiths related to the theme, using several key words. The result of this research is that the purpose of education according to Al-Ghazali emphasizes religious and moral education. According to him, the meaning and purpose of Islamic education is education that seeks and aims in the process of forming a complete human being. As for making a curriculum, Al Ghazali has two tendencies, namely a tendency towards religion and a pragmatic tendency. As for the material aspects of Islamic education according to Al Ghazali's thoughts include: faith, morals, reason, social and physical education. The purpose of education according to the hadith of the Prophet Muhammad is to create humans who have noble character, to create humans who have a balanced life between the world and the hereafter, to create people who are useful and efficient for themselves, their families, communities and nations and even benefit the world. who are trustworthy and responsible, Realizing humans who are integrated with the progress of the world without leaving the noble values ​​contained in Islamic morals. According to him, a good teacher, apart from being intelligent and perfect in mind, must also have commendable qualities. The characteristics that must be possessed by a student are humility, purify oneself from all evil, obey and istiqamah. Meanwhile, the evaluation of education is all forms of activities related to their respective responsibilities in the educational process. The purpose of education in the perspective of hadith can be classified as follows; tarbiyah jismiyah (physical education), tarbiyah ruhiyah, tarbiyah aqliyyah (aqal education), tarbiyah wijdaniyyah (emotional education), tarbiyyah al-khuluqiyyah (moral education), and tarbiyah ijtima'iyyah (educational education). social).Keywords : Educational Goals, Al-Ghazali, Hadith Perspectives